2019
DOI: 10.1002/mnfr.201900603
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus and Bifidobacterium Improves Physiological Function and Cognitive Ability in Aged Mice by the Regulation of Gut Microbiota

Abstract: Scope Age‐related degeneration is associated with imbalances of gut microbiota and its related immune system, thus gut microbiota dysbiosis is considered to be a key target to improve senescence. The potential roles of probiotics on physiological function and cognitive ability in aged mice are investigated in this study. Methods and results Lactobacillus casei LC122 or Bifidobacterium longum BL986, are orally administrated for 12 weeks, and the anti‐aging effects, as well as the composition and function of gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
213
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(227 citation statements)
references
References 47 publications
13
213
0
1
Order By: Relevance
“…2a). Because other Lactobacillus strains have previously been implicated in improving memory in mice, humans, and rats: e.g., L. rhamnosus JB-1 in mice [5], L. casei LC122 in aged mice [22], L. helveticus ROO52 in humans [6], and L. acidophilus strains CUL60 and CUL21 (in combination with bifidobacteria) in rats [8]. We focused our remaining studies on Lactobacillus, in particular L. reuteri that was identified in this study.…”
Section: Resultsmentioning
confidence: 99%
“…2a). Because other Lactobacillus strains have previously been implicated in improving memory in mice, humans, and rats: e.g., L. rhamnosus JB-1 in mice [5], L. casei LC122 in aged mice [22], L. helveticus ROO52 in humans [6], and L. acidophilus strains CUL60 and CUL21 (in combination with bifidobacteria) in rats [8]. We focused our remaining studies on Lactobacillus, in particular L. reuteri that was identified in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, muscle mass and the muscle mass/body weight ratio were increased following natural microbiota seeding in antibiotic-treated mice (Nay et al, 2019). In terms of bacterial species that may positively impact muscle mass, oral gavage with Lactobacillus casei or Bifidobacterium longum increased the muscle mass/body weight ratio without affecting body weight (Ni et al, 2019).…”
Section: Role Of the Gut Microbiome And Short-chain Fatty Acids On Skmentioning
confidence: 98%
“…Treadmill endurance capacity was reduced in conjunction with increased ex vivo muscle fatigability in antibiotic-treated mice (Nay et al, 2019;Okamoto et al, 2019), and swimming endurance capacity was reduced in young GFM, when compared with conventionallyraised mice (Huang et al, 2019). In terms of bacterial taxa that may underlie the maintenance of physical function, oral gavage with the bacterial species Lactobacillus casei or Bifidobacterium longum increased grip strength in young mice (Ni et al, 2019). Colonization of young GFM with Eubacterium rectale or Clostridium coccoides increased swim time to exhaustion, when compared with uncolonized GFM (Huang et al, 2019).…”
Section: Role Of the Gut Microbiome And Short-chain Fatty Acids On Phmentioning
confidence: 99%
“…[135] Of note, apart from the benefits for liver diseases, our team recently investigated the role of two major probiotics (Lactobacillus casei LC122 and Bifidobacterium longum BL986) in anti-aging via regulation of the gut microbiota. [136] A prebiotic is a substrate selectively utilized by the host microbiome that is beneficial for host health. Catry et al first demonstrated that inulin-type fructan (ITF) supplementation in apolipoprotein E knockout (ApoE −/− ) mice fed a N-3 polyunsaturated fatty acid-depleted diet effectively reduced hepatic inflammation by suppressing NF-B signaling.…”
Section: Probiotics Prebiotics and Symbioticsmentioning
confidence: 99%